ТЕОРЕТИЧЕСКИЕ ОСНОВЫ ОБУЧЕНИЯ ПЕРЕГОВОРАМ В КОНТЕКСТЕ ПРОФЕССИОНАЛЬНО-ДЕЛОВОГО ОБЩЕНИЯ - Сейтенова, В.А. (SCIENCE and SOCIETY, 2024)
The choice of theme is dictated by the necessity of educating to the professionally-business communication in the Russian language of the specialists in the field of commercial activity. In article characterized business negotiations realized in the course of commercial activity. The analysis of verbal negotiations as forms of cooperation of subjects is given at consideration of terms of draft contract on the settlement of a transaction. On the basis of description of the general classification of types of information an author distinguishes those parameters that are substantial during a professional communication.
Keywords: argumentation; interaction; rapport; mutual understanding; contact; professional speech; communication; palaver; theory speech; in article; business dialogue